Delivering Home Hemodialysis: Is There Still a Role for Real‐Time Treatment Monitoring?. Issue 2 (30th November 2014) - Marshall, Mark R.; Pierratos, Andreas; Pauly, Robert P.
Abstract Remote real‐time treatment monitoring for home hemodialysis (HHD) was driven by concerns over patient safety in the early era of HHD. However, decades of clinical experience supported by objective data suggest that HHD is very safe and that remote monitoring is unlikely to avert serious adverse events. As a result, such remote monitoring is not routinely offered in the current era and is generally considered an unnecessary expense. However, a one‐size‐fits‐all approach to abandon remote monitoring may overlook potential opportunities: to improve the clinical care of patients dialyzing at home; and to give patients the confidence to perform HHD in an unsupervised setting.